Reading and spelling difficulties in high school students: Causes and consequences - Shankweiler, Donald; Lundquist, Eric; Dreyer, Lois G; Dickinson, Cheryl C (Reading and Writing, 1996)
Basic skills in reading and spelling and supporting metalinguistic abilities were assessed in ninth and tenth grade students in two school settings. Students attending a private high school for the learning disabled comprised one group and the other comprised low to middle range students from a public high school. Both the LD students and the regular high school students displayed deficiencies in spelling and in decoding, a factor in reading difficulty that is commonly supposed to dwindle in importance after the elementary school years. Treating the overlapping groups as a single sample, multiple regression analysis was used to investigate the contribution of nonword decoding skill and phonological and morphological awareness to spelling ability. The analysis revealed that decoding was the major component, predicting about half of the variance in spelling. The effect of phonological awareness was largely hidden by its high correlation with decoding, but was a significant predictor of spelling in its own right. Morphological awareness predicted spelling skill when the words to be spelled were morphologically complex. An additional study showed that differences in decoding and spelling ability were associated with differences in comprehension after controlling for reading experience and vocabulary. Even among experienced readers individual differences in comprehension of text reflect efficiency of phonological processing at the word level.
61 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/021-152-771-398-307 tex.type: [object Object]
Keywords: Decoding; High school poor readers; Metalinguistic abilities; Spelling; dept.edu